Analisis Perbedaan Tingkat Kepuasan Pasien Rawat Jalan Terhadap Kualitas Pelayanan Pendaftaran Pada Metode Online Dan Onsite Di RSUD Bagas Waras Klaten: Analysis Of Differences In Outpatient Satisfaction Levels On The Quality Of Registration Services In Online And Onsite Methods At Bagas Waras Klaten Hospital - Rofiqoh Arifatul Khuzaimah; Sri Sugiarsi; Sri Mulyono (Indonesian Journal of Health Information Management, 2026)
Customer satisfaction is one of the benchmarks for service quality. Hospitals that are one of the providers of health services are required to provide easy access to health services and also improve the quality and maintaince hospital service standards. One way to improve the quality of service is the existence of online registration in addition to onsite registration. The purpose of this study was to determine the difference in the level of patient satisfaction with online and onsite registration services at Bagas Waras Klaten Hospital. This type of research is a comparative analytical study, with the total population of all outpatients in December 2022. Sampling using the minimum sample size formula of unpaired numerical comparative studies of two groups of one-time measurements n1 = n2, the result of which was 55 patients. The sampling technique uses sequansial random sampling. How to collect data using questionnaires, observations, and unstructured interviews. The data analysis of this study was univariate and bivariate, with online satisfaction results being 98.2% and dissatisfied 1.8%, onsite satisfaction 89% and dissatisfied 11%. Based on the results of the Man Withney test, the value of A Symp sig = 0.831 then Ho was accepted and Ha was rejected, which means that there is no difference in outpatient satisfaction with the quality of registration services in the online and onsite methods